A simple test for asymptotic stability in some dynamical systems (2014)
ABSTRACT: In this paper we analyze asymptotic stability of the dynamical system =f(x) defined by a C1 function is and open set. We ontain a criterion of satabilty for the equilibrium solution when the vector field f satisfies